Development of an intravenous chemotherapy intervention for children and adolescents with cancer administered by their parents at home (INTACTatHome) - Louise Ingerslev Roug; Martha Krogh Topperzer; Rikke Thenning Michelsen; Mary Jarden; Ayo Wahlberg; Lisa Lyngsie Hjalgrim; Helena Hansson (BMC, 2023)
Abstract Background Families of children and adolescents with cancer strive to maintain routines and normalcy during the child's treatment trajectory that requires frequent hospital visits. Intravenous chemotherapy at home can reduce time spent on the frequent hospital visits and mitigate disruption in daily life. Studies on home chemotherapy for children and adolescents with cancer are limited, as is knowledge of family and health care professionals' needs, and knowledge required to inform adaptation or replication of interventions in other settings. The aim of this study was to develop and describe an evidence-based home chemotherapy intervention that is feasible and safe for children and adolescents and suitable for future feasibility testing. Methods The Medical Research Council's guidance for developing complex interventions in health care and the framework of action developed by O'Cathain et al. was used as theoretical frameworks to structure the development process. A literature search, an ethnographic study, and interviews with clinical nurse specialists from adult cancer departments formed the evidence base. Educational learning theory to support and understand the intervention was identified. Stakeholder perspectives were explored in workshops with health care professionals and parent-adolescent interviews. Reporting was qualified using the GUIDED checklist. Results A stepwise educational program to teach parents how to administer low-dose chemotherapy (Ara-C) to their child at home and a simple and safe administration procedure were developed. Key uncertainties were identified, including barriers and facilitators impacting future testing, evaluation, and implementation. Causal assumptions and reasoning for how the intervention leads to short-term outcomes and long-term impact were clarified in a logic model. Conclusions The iterative and flexible framework allowed for integration of existing evidence and new data and was successfully applied to the development process. The detailed report on the development process of the home chemotherapy intervention can enhance adaptation or replication of the intervention to other settings and thereby mitigate family disruption and stress of frequent hospital visits for these treatments. The study has informed the next phase of the research project that aims to test the home chemotherapy intervention in a prospective single-arm feasibility study. Trial registration ClinicalTrials.gov ID: NCT05372536.